Self-medication with proton pump inhibitors among physicians in Bosnia and Herzegovina: a cross-sectional study - Jovanovic, Predrag; Bokan, Goran; Basic Denjagic, Mirela; Salkic, Nermin; Kurtcehajic, Admir; Gavric, Aleksandar; Ljuca, Kenana; Tadic, Mario; Mesihovic, Rusmir; Hauser, Goran; Zerem, Dina (Frontiers in Medicine, 2026)
BackgroundProton pump inhibitors (PPIs) are widely used for the treatment of acid-related disorders, but inappropriate or prolonged use carries potential health risks. Physicians, due to their access to medication and clinical knowledge, may be prone to self-medicating with PPIs without appropriate oversight.ObjectiveTo assess the prevalence and patterns of personal PPI use and self-medication among practicing physicians in Bosnia and Herzegovina, and to identify demographic and professional predictors of such behavior.MethodsA cross-sectional, questionnaire-based survey was conducted among 448 physicians who responded to the study invitation, out of approximately 600 invited, from various healthcare levels in Bosnia and Herzegovina between January and May 2025. The survey collected data on PPI use history, consultation behavior, awareness of adverse effects, and adherence to treatment guidelines. Multivariable logistic regression was used to identify independent predictors of self-medication.ResultsA total of 65.4% of respondents reported past PPI use, during their medical practice, and 31.7% were current users. Over half (52.2%) admitted using PPIs without consulting another physician, and only 17.4% referred to clinical guidelines prior to use. Occasional use was the most common pattern (59.0%), while adverse effects were rarely reported (1.8%). No demographic or professional variable was significantly associated with self-medication with PPIs (defined as PPI use without consulting another physician) in the multivariable analysis.ConclusionSelf-medication with PPIs is highly prevalent among physicians and frequently occurs without clinical consultation or adherence to guidelines. This behavior appears to be widespread across age groups, sexes, and care levels, highlighting the need for institutional interventions that promote rational prescribing and raise awareness about responsible self-care within the medical profession.